Altered Synaptic Vesicle Release and Ca2+ Influx at Single Presynaptic Terminals of Cortical Neurons in a Knock-in Mouse Model of Huntington’s Disease - Chen, Sidong; Yu, Chenglong; Rong, Li; Li, Chun Hei; Qin, Xianan; Ryu, Hoon; Park, Hyokeun (Frontiers in Molecular Neuroscience, 2018)
Huntington’s disease (HD) is an inherited neurodegenerative disorder caused by the abnormal expansion of CAG repeats in the huntingtin gene, which leads to progressive loss of neurons starting in the striatum and cortex. One possible mechanism for this selective loss of neurons in the early stage of HD is altered neurotransmission at synapses. Despite the recent finding that presynaptic terminals play an important role in HD, neurotransmitter release at synapses in HD remains poorly understood. Here, we measured synaptic vesicle release in real time at single presynaptic terminals during electrical field stimulation. We found the increase in synaptic vesicle release at presynaptic terminals in primary cortical neurons in a knock-in mouse model of HD (zQ175). We also found the increase in Ca2+ influx at presynaptic terminals in HD neurons during the electrical stimulation. Consistent with increased Ca2+-dependent neurotransmission in HD neurons, the increase in vesicle release and Ca2+ influx was rescued with Ca2+ chelators or by blocking N-type voltage-gated Ca2+ channels, suggesting N-type voltage-gated Ca2+ channels play an important role in HD. Taken together, our results suggest that the increased synaptic vesicles release due to increased Ca2+ influx at presynaptic terminals in cortical neurons contributes to the selective neurodegeneration of these neurons in early HD and provide a possible therapeutic target.